Dietary intervention reprograms bone marrow cellular signaling in obese mice - Zheng, Yuxuan; Yan, Jiren; Zhang, Xiaofu; Cui, Hailong; Wei, Zhenyuan; Li, Xiaoying; Wang, Qiuyu; Zhong, Biao (Frontiers in Endocrinology, 2023)
The current study aimed to investigate the pathogenesis of obesity-induced impaired bone mass accrual and the impact of dietary intervention on bone density in the mouse model of obesity. Mice were fed with chow diet (CD) for 10 months, high-fat-diet (HFD) for 10 months, or HFD for 6 months then transferred to chow diet for 4 months (HFDt). Weight loss and decreased intrahepatic lipid accumulation were observed in mice following dietary intervention. Additionally, HFD feeding induced bone mass accrual, while diet intervention restrained trabecular bone density. These changes were further reflected by increased osteogenesis and decreased adipogenesis in HFDt mice compared to HFD mice. Furthermore, HFD feeding decreased the activity of the Wingless-related integration site (Wnt)-β-Catenin signaling pathway, while the Wnt signaling was augmented by diet intervention in the HFDt group. In conclusion, our findings suggest that a HFD inhibits bone formation and that dietary intervention reverses this inhibition. Furthermore, the dietary intervention was able to compensate for the suppressed increase in bone mass to a level comparable to that in the CD group. Our study suggests that targeting the Wnt signaling pathway may be a potential approach to treat obesity-induced impaired bone mass accrual.